2016
DOI: 10.1057/s41271-016-0038-8
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations due to selected infections caused by opportunistic premise plumbing pathogens (OPPP) and reported drug resistance in the United States older adult population in 1991–2006

Abstract: The Flint Water Crisis -due to changes of water source and treatment procedures -has revealed many unsolved social, environmental, and public health problems for US drinking water, including opportunistic premise plumbing pathogens (OPPP). The true health impact of OPPP, especially in vulnerable populations such as the elderly, is largely unknown. We explored 10 8 claims in the largest US national uniformly collected data repository to determine rates and costs of OPPP-related hospitalizations. In 1991-2006, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Over the last decade, the interest in premise plumbing from the water industry has increased. Numerous studies have investigated different issues surrounding premise plumbing, such as corrosion [78][79][80][81] and the growth of opportunistic pathogens [82][83][84][85][86][87][88]. Premise plumbing systems are an area of the distribution system that can be overlooked by water utilities, since most premise plumbing systems are not owned or maintained by the utility and most drinking water regulations do not address premise plumbing, with the exception of the Lead and Copper Rule (LCR).…”
Section: Nitrification In Premise Plumbingmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last decade, the interest in premise plumbing from the water industry has increased. Numerous studies have investigated different issues surrounding premise plumbing, such as corrosion [78][79][80][81] and the growth of opportunistic pathogens [82][83][84][85][86][87][88]. Premise plumbing systems are an area of the distribution system that can be overlooked by water utilities, since most premise plumbing systems are not owned or maintained by the utility and most drinking water regulations do not address premise plumbing, with the exception of the Lead and Copper Rule (LCR).…”
Section: Nitrification In Premise Plumbingmentioning
confidence: 99%
“…While coliform bacteria and HPC are more traditional bacteria monitored in DWDS, opportunistic premise plumbing pathogens (OPPP) have been the focus of numerous studies in recent years due to the increasing prevalence of hospitalizations due to infections caused by OPPP. Between 1991 and 2006, there were 7,933 cases of Legionnaires' disease (only diagnosed from 1997-2006) reported; however, this number continues to rise each year with the number of reported cases reaching 6,079 in 2015 and 10,000 in 2018 alone [87,106,107]. In the same 1991-2006 study, Naumova et al found that there were 544,643 hospitalizations from infections caused by Pseudomonas, and 15,861 hospitalizations due to unidentified gram-negative anaerobic bacteria in records for patients 65 years and older enrolled in Medicaid or Medicare [87].…”
Section: Microbial Regrowth and Opportunistic Premise Plumbing Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…The main advantages that the biofilm confer on the pathogen were the ability to persist, spread, and resist treatments. In the United States, three plumbing-associated opportunistic pathogens (i.e., Legionella pneumophila, Mycobacterium avium, and Pseudomonas aeruginosa) are linked to cause~41,000 infections per year, mostly affecting elderly populations and immunocompromised individuals [29,92].…”
Section: Microbial Composition In Dwds Biofilms Influencing Water Quamentioning
confidence: 99%
“…They can reside in drinking-water distribution systems and premise plumbing (the portion of the water distribution system inside buildings) [11]. The three pathogens have been referred to as opportunistic premise plumbing pathogens because of the attributes listed above and their tendency to infect individuals who are older, immunosuppressed and/or have pre-existing chronic diseases [18].…”
Section: Introductionmentioning
confidence: 99%